2016
DOI: 10.1111/codi.13306
|View full text |Cite
|
Sign up to set email alerts
|

Timing of adjuvant chemotherapy in colorectal cancer

Abstract: In this large retrospective study, the standard prognostic factors impacted on survival whereas the timing of adjuvant therapy did not. Patients with delayed adjuvant chemotherapy may have worse prognostic factors which could play a major role in their poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 15 publications
0
14
1
Order By: Relevance
“…Despite the high incidence and mortality rate of CRC in Brazil, few studies have comprehensively described and characterized the main clinicopathological features of Brazilian patients with CRC (19,20). Therefore, this study aimed to characterize the clinicopathological aspects of CRC patients, to determine their genetic ancestry, and to identify whether the genetic ancestry can influence patients' clinicopathological features and disease outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high incidence and mortality rate of CRC in Brazil, few studies have comprehensively described and characterized the main clinicopathological features of Brazilian patients with CRC (19,20). Therefore, this study aimed to characterize the clinicopathological aspects of CRC patients, to determine their genetic ancestry, and to identify whether the genetic ancestry can influence patients' clinicopathological features and disease outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Dos Santos L.V. et al, [15] defined that a longer interval of either six or eight weeks before PAC would firmly reduce 5-year OS. Moreover, Sun Z. et al, [16] emphasized the importance of the timely initiation, which suggested delays beyond 6 weeks were associated with a compromised survival.…”
Section: Discussionmentioning
confidence: 99%
“…One of the largest series evaluating the impact of AC in colorectal cancer showed that a delay in the initiation of AC has a minor impact on survival. On Cox regression analysis, only pathologic stage, angiolymphatic invasion, histological grade, emergency surgery, preoperative therapy, and age were significant factors influencing OS [ 19 ]. The interval between surgery and AC was not significant.…”
Section: Discussionmentioning
confidence: 99%